Population date of Great Cormorant at the area of the Hortobágy Fish Farm Co. - Tóth, Norbert; Gyüre, Péter; Posta, János; Juhász, Lajos (Acta Agraria Debreceniensis, 2013)
Hungary’s great cormorant stock did not use to be a considerable one before the 1980s. After that, their number has been rising significantly. The size of the stock now is rather stagnating or slightly growing. The presence of cormorants has been significant around ponds of the Hortobágy Fish Farm in the past few years. Due to considerable fish consumption of cormorants it is essential to know which and what kinds of units of the ponds (spawning, supply, and market) are preferred by the birds in order to see to adequate protection. The aim of our research was to discover any differences in the number of cormorants present at particular units of the fishpond system and certain ponds of equal kinds within them. Our observations were in line with the methods used in ornithological researches. The experiment took place between April and October 2012 on a monthly basis. According to the results we found relevant differences in the number of cormorants based on the seasons and months as well. This fact was supported by statistical data. During the autumn and winter birds prefer supply and market purpose ponds while their presence here is vanishing during the summer. Relevant presence of cormorants around the area of the Old Fishponds (70 to 200 specimens) might be due to lack of disturbance and large sizes of the ponds. Our research has great scientific relevance since it is vital to be aware of the preferred periods and areas in order to maintain effective protection; this way alerting activities can be applied in a more harmonized way. By keeping our research up as a monitoring activity, we will be able to receive more precise data later on.